Blenderized Watermelon Consumption Improves BMI, BMI Percentile, Body Fat, and A1C in Overweight or Obese Children. (14th June 2022) - Daughtry, Jaikko; Rasmussen, Caitlin; Rosas, Martin; Zhang, Liyue; Lu, Stephanie; Hooshmand, Shirin; Kern, Mark; Liu, Changqi; Hong, Meeyoung
Abstract: Objectives: Childhood obesity increases risk factors related to metabolic diseases and watermelon's bioactive components can help reduce these risk factors. However, no study has investigated the effects of watermelon juice containing rind in children with obesity or overweight. The objective of this study was to examine the effects of blenderized watermelon with rind on anthropometric and clinical markers of BMI, body fat, glucose, insulin, A1C, inflammation, lipid profile, liver function enzymes, and satiety hormones. Methods: A randomized, cross over clinical design was implemented where children (n = 17, 8 females/9 males, age 12.9 ± 2.0 years) consumed one cup (240 mL, 70 kcal) of blenderized watermelon juice with rind or isocaloric sugar juice (control) every day for eight weeks with a four-week washout period. Results: Significantly lower BMI ( p = 0.032) and BMI percentile ( p = 0.038), were observed when comparing eight weeks of watermelon juice intake to eight weeks of sugar juice intake. Sugar juice consumption increased BMI percentile ( p = 0.014) compared to baseline. A decrease in body fat, measured with Bod Pod within watermelon juice consumption was observed, but not in sugar juice ( p = 0.047). Body fat was lower in watermelon juice than sugar juice intake at week eight ( p = 0.036). A decrease in A1C was observed within watermelon juice intake ( p = 0.008) but not with sugar juice intake. A1C watermelon juice week eight was lower than sugar juice week eight ( p = 0.012). No significant differences between trials were observed for leptin, ghrelin, c-reactive protein, glucose, insulin, lipid profiles, and liver function enzymes. Conclusions: The results support that blenderized watermelon juice consumption improved cardiometabolic risk factors including BMI, BMI percentile, body fat, and A1C in desirable directions. To our knowledge, this is the first study examining the effects of watermelon juice with flesh and rind consumption on cardiometabolic risk factors in overweight/obese children. Our study shows that watermelon is a potential alternative to unhealthful snacks for reducing the risk factors related to obesity. Funding Sources: The National Watermelon Promotion Board [NWPB 19-20].